Manifestatie in de Expo-hal tgv. 10 jaar wereldwinkels: 'Maak een begin met echte ontwikkelingshulp' - Stegeman, Jan,
Manifestatie in de Expo-hal tgv. 10 jaar wereldwinkels: 'Maak een begin met echte ontwikkelingshulp'.